An Achaemenid Symbol. I. A Farewell to “Fravahr” and “Ahuramazda” - Shabbazi, A. Sh.
ersch. 1975; Western scholars have maintained that winged-circle, often with upper part of a man, symbolizes Ahuramazda, as it symbolized Aššur in Assyria; Iranians that it represents the fravahr or soul-duplicate and guardian angel. Neither theory is convincing; a further article will examine the proposal that it represents the Khwrenah (ḫvarnah) “glory, fortune” of the Iranian king or nation.